Alterations in psychosocial health of people affected by asbestos poisoning - Miguel Clemente; Adela Reig-Botella; Juan Carlos Prados (Universidade de São Paulo, 2015)
OBJECTIVE To analyze the state of psychosocial and mental health of professionals affected by asbestos. METHODS A cross-sectional study was conducted with 110 professionals working in the Ferrolterra region of Spain, who were affected by asbestos poisoning. This group was compared with a group of 70 shipyard workers with no manifestation of work-related diseases. All the participants were male with a mean age of 67 years. This study was conducted in 2013, between January and June, and used the SCL-90 questionnaire by Derogatis as its primary measure for research. This questionnaire consists of 9 variables that measure psychosomatic symptoms. In addition, an overall index of psychosomatic gravity was calculated. The participants were also asked two questions concerning their overall perception of feeling good. Data were analyzed by ANOVA and logistic regression. RESULTS Participants affected by asbestos poisoning showed high occurrence rates of psychological health variables such as somatization, obsessive-compulsive, interpersonal sensitivity, depression, anxiety, hostility, phobic anxiety, paranoid ideation, psychoticism, and global severity index. CONCLUSIONS Social interaction as a differentiating factor between workers affected by work-related chronic syndromes as compared to healthy participants will possibly aid in the development of intervention programs by improving the social network of affected individuals.